Clinical characteristics of neuro-Behcet’s disease in Japan: a multicenter retrospective analysis - Hirohata, Shunsei (Springer Japan, 2011)
To delineate the clinical characteristics of neuro-Behçet’s disease (NBD), a multicenter retrospective survey was performed in BD patients who had presented any neurological manifestations between 1988 and 2008. The diagnosis of acute NBD, chronic progressive (CP) NBD, and non-NBD was confirmed by retrospective review of clinical records. Data on a total of 144 patients were collected; 76 with acute NBD, 35 with CP NBD, and 33 with non-NBD. High-intensity lesions on T2-weighted magnetic resonance imaging (MRI) were found in 60.5% of the patients with acute NBD, 54.2% with CP NBD, and 42.4% with non-NBD, whereas brainstem atrophy was observed in 7.5% with acute NBD, 71.4% with CP NBD, and 9.0% with non-NBD. The cerebrospinal fluid (CSF) cell count was prominently elevated in patients with acute NBD, but was normal in about 15% of those with CP NBD. The sensitivity and specificity of the CSF cell count for the diagnosis of acute NBD versus non-NBD were 97.4 and 97.0%, respectively (cut-off 6.2/mm(3)). The sensitivity and specificity of CSF interleukin (IL)-6 for the diagnosis of CP NBD versus the recovery phase of acute NBD were 86.7 and 94.7%, respectively (cut-off 16.55 pg/ml). The results indicate that elevation of the CSF cell count and CSF IL-6 and the presence of brainstem atrophy on MRI are useful for the diagnosis of NBD.